French Reasons for Alliance through Yankee Eyes, 1775-1778 - Pereira, Trevor J. (My University, 2015)
This paper will examine early American diplomacy during the quest for American independence. This research will discuss why France decided to support the independent movement of the colonists, and how the French conducted their diplomacy with the American revolutionaries. To comprehend the French objectives, it is important to understand why France wished to weaken the British Empire. Moreover, French losses during the 1763 Treaty of Paris, left them wanting revenge on the British. France supported American independence, but had to support the Americans discreetly and declare neutrality in the Revolutionary War, so as to keep the British unaware of the French clandestine aid to the Americans. This paper will examine how America signed its first treaties, the Treaty of Amity and Commerce and the Treaty of Alliance with France in 1778, that was greatly advantageous to America. This research will conclude with the diplomatic engagements after the treaties were signed, just before American diplomacy shifted its focus to making peace with Great Britain.
Keywords: Treaty of Paris (1763)